OSSGrab: software repositories and app store mining tool - Awang Abu Bakar, Normi Sham; Mahmud, Iqram (IACSIT PRESS, 2013)
One of the main challenges for empirical researchers is to collect software data. However, with the emergence of the open source repositories, they have a large amount of software to choose from for mostly any types of research. Moreover, the mining software repositories research area can be further extended to the mobile apps mining. Generally, searching through large software repositories to look for specific systems can be a daunting task. Therefore, there is a need to build a tool which can expedite and ease the search process so that the researchers can focus on analyzing the data. Our paper presents a tool, OSSGrab, which can be used to automate the search process in the SourceForge software repository, as well as searching through the Android app store. As a result, this tool has managed to save tremendous amount of time that need to be spent for data collection.